2018
DOI: 10.1002/chem.201705232
|View full text |Cite
|
Sign up to set email alerts
|

A Polycarboxyl‐Decorated FeIII‐Based Xerogel‐Derived Multifunctional Composite (Fe3O4/Fe/C) as an Efficient Electrode Material towards Oxygen Reduction Reaction and Supercapacitor Application

Abstract: Low cost, non-noble metal catalysts with a good oxygen reduction reaction (ORR) activity comparable to that of platinum and also having good energy storage properties are highly desirable but challenging. Several challenges are associated with the development of such materials. Herein, we demonstrate a new polycarboxyl-functionalised Fe -based gel material, synthesised following a solvothermal method and the development of its composite (Fe O /Fe/C) by annealing at optimised temperature. The developed composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Deconvoluted N 1s spectra of the TAB-DFP-nCOFs indicate the presence of three distinct peaks at (i) 398.95 eV, corresponding to the imine nitrogen, (ii) 399.35 eV, associated with pyridinic nitrogen, and (iii) 399.95 eV, which is attributed to quaternary nitrogen (protonated pyridine on the surface) in the TAB-DFP-nCOF matrix (Figure S15e and Table S4). Upon the addition of nanoparticles, there was a significant shift (0.5 eV) of the N -pyridine peak compared to the pristine nCOF (Figure S15f and Table S4), with all of the other peaks remaining unchanged. This shift toward low binding energies strongly indicates electron transfer from pyridinic nitrogen to the nanoparticles, as described by Pan et al, thus demonstrating that γ-Fe 2 O 3 NPs interact with the nCOF surface through N–Fe bonds. , …”
Section: Resultsmentioning
confidence: 99%
“…Deconvoluted N 1s spectra of the TAB-DFP-nCOFs indicate the presence of three distinct peaks at (i) 398.95 eV, corresponding to the imine nitrogen, (ii) 399.35 eV, associated with pyridinic nitrogen, and (iii) 399.95 eV, which is attributed to quaternary nitrogen (protonated pyridine on the surface) in the TAB-DFP-nCOF matrix (Figure S15e and Table S4). Upon the addition of nanoparticles, there was a significant shift (0.5 eV) of the N -pyridine peak compared to the pristine nCOF (Figure S15f and Table S4), with all of the other peaks remaining unchanged. This shift toward low binding energies strongly indicates electron transfer from pyridinic nitrogen to the nanoparticles, as described by Pan et al, thus demonstrating that γ-Fe 2 O 3 NPs interact with the nCOF surface through N–Fe bonds. , …”
Section: Resultsmentioning
confidence: 99%
“…The porous carbons PC600, PC800, and PC1000 have been demonstrated as efficient electrode materials with the respective specific capacitances of 213.1, 129.1, and 114.3 F g −1 . 191 When used for capacitive deionization, PC800 showed a notable desalination capacity of 25.16 mg g −1 at 1.4 V in 500 mg L −1 aqueous NaCl solution. It showed that MOG-derived porous carbons are potential electrode materials for high-performance water desalination.…”
Section: Metal–organic Gels For Supercapacitorsmentioning
confidence: 99%
“…Devi et al developed an Fe 3+ -based MOG of H 4 BTA that bears peripheral poly-carboxyl groups. 191 The FeBTA MOG was used to fabricate the Fe 3 O 4 /Fe/C composite via thermal treatment at 700 °C. The composite Fe 3 O 4 /Fe/C particles of ca.…”
Section: Metal-organic Gels For Supercapacitorsmentioning
confidence: 99%
“…[46][47][48][49] These peaks are fitted using a shakeup satellite and two spin-orbit doublets, which originate from the Fe 3+ and Fe 2+ states. [46][47][48] The area ratio of Fe 3+ /Fe 2+ in the spectrum is approximately 2, indicating that the material deposited on the FTO substrate is Fe 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%